POLITIK HUKUM PERUBAHAN STATUS PEGAWAI KOMISI PEMBERANTASAN KORUPSI MENJADI APARATUR SIPIL NEGARA BERDASARKAN PERATURAN PEMERINTAH NOMOR 41 TAHUN 2020 TENTANG PENGALIHAN PEGAWAI KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI MENJADI APARATUR SIPIL NEGARA - Eka Safitri; Zulwisman Zulwisman; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the state institutions supporting bodies in the Indonesian constitutional structure system is the Corruption Eradication Commission, hereinafter abbreviated as the KPK, the presence of the Corruption Eradication Commission (KPK) To carry out the eradication of corruption, the corruption eradication commission requires the support of professional, high integrity, moral and human resources. responsible and consistent in carrying out their duties, powers and obligations in accordance with the provisions of laws and regulations. However, on July 24, 2020, Government Regulation Number 41 of 2020 concerning the Transfer of Corruption Eradication Commission Employees to State Civil Servants was enacted. This regulation came out following the issuance of Law No. 19 of 2019 concerning the Corruption Eradication Commission, but this change in the status of KPK employees has reaped pros and cons in the public because many think that this status change will interfere with the independence and performance of the KPK, because the change in the status of KPK employees to State Civil Apparatus (ASN)This research uses a typology of normative legal research or what is also called doctrinal legal research, which deals more specifically with legal principles. In this study the authors use descriptive research characteristics, because the authors describe the Regulatory Structuring of Independent State Institutions in the Structure of the Indonesian State Administration System.The results of the research conducted by the author is that this status will interfere with the independence and performance of the KPK, because the transfer of the status of KPK employees to the State Civil Apparatus (ASN) certainly makes the KPK also subject to the regulations of the State Civil Apparatus. The change of status to ASN also affects the recruitment of employees, including competency enhancement which cannot be done alone and specifically the provisions of Article 9 paragraph (1) and paragraph (2) of the PP are related to salary and benefits. Syarif explained, if it is concluded, there are three components of the salary for KPK employees based on the PP. Respectively, namely salary, allowances, and special allowances that can be given if they are still lackingKeywords: Legal politics, Independent Institutions, KP